Electrical discharge machining of boron carbide-graphene nanoplatelets composites. Issue 3 (March 2022) - Wang, Aiyang; Hu, Lanxin; He, Qianglong; Liu, Chun; Tian, Tian; Zhang, Zhixiao; Yi, Chenhong; Zhang, Fan; Wang, Weimin; Wang, Hao; Fu, Zhengyi
Abstract: Boron carbide (B4 C) composites containing 0–10 wt.% graphene nanoplatelets (GNPs) were consolidated using hot pressing at 1950 °C for 60 min under 30 MPa in an argon atmosphere. Their electrical discharge machining (EDM) characteristics were evaluated for the first time. Additionally, the effects of GNPs on the microstructure, electrical conductivity, material removal rate (MRR), and surface roughness (Ra ) of B4 C composites were investigated. The results show that the B4 C composite containing 10 wt.% GNPs exhibited the highest electrical conductivity of 4997 S·m −1 because of the formation of GNPs conductive networks. Under a fine machining condition, the MRR of the B4 C composite was enhanced by 43.5 % (from 6.55 to 9.40 mm 3 min −1 ) compared with that of monolithic B4 C. Furthermore, the Ra decreased to 1.12 μm, which was significantly lower than that of pure B4 C (2.44 μm). Scanning electron microscope and energy disperse spectroscopy analysis of the EDM surfaces were used to determine that the main material removal mechanisms for B4 C composites with less than 2 wt.% GNPs were spalling and melting. As the GNPs content increased, B4 C grain fallout, melting, and evaporation became more dominant. The other mechanisms, including thermal shock and oxidation, are also discussed in detail.